Pengabdian Masyarakat Dalam Pengelolaan Lahan Rumah Tangga Berbasis Tanaman Pangan - Untari, Dhian Tyas (Yayasan Daarul Huda Kruengmane, 2024)
Another basic need that humans must fulfill is shelter. According to several reference sources, a board is a place where you live, in this case a house, whether you own it, rent it or share it. Of these two terms, the basic needs of human life, it is interesting to dissect them. Based on this, this community service activity aims to provide education to the general public about opportunities for using land as a medium for growing food. This activity was carried out in residents of Cijengkol Village, Setu District - Bekasi.